2015
DOI: 10.1073/pnas.1508345112
|View full text |Cite
|
Sign up to set email alerts
|

Stress impairs cognitive flexibility in infants

Abstract: In human adults, learning and memory under acute stress are characterized by an increased use of rigid habitual response strategies at the cost of flexible cognitive strategies. The immediate effects of stress on cognitive functioning early in life are not well understood. Here we show experimentally that acute stress leads human infants to perform habitual behavior rigidly. We found that 15-mo-old infants exposed to stress thereafter kept performing a previously effective action, even after the action suddenl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…This may also be directly related to the behavioral effects observed, since coping styles and personalities are affected by circulating CORT levels. For example, a more bold personality was seen in Florida Scrub-jays exposed to elevated glucocorticoid levels on day 11 post hatch34 and steroids also affect memory and learning abilities3536.…”
Section: Discussionmentioning
confidence: 99%
“…This may also be directly related to the behavioral effects observed, since coping styles and personalities are affected by circulating CORT levels. For example, a more bold personality was seen in Florida Scrub-jays exposed to elevated glucocorticoid levels on day 11 post hatch34 and steroids also affect memory and learning abilities3536.…”
Section: Discussionmentioning
confidence: 99%
“…The profound influence of stress on individuals' ability to adjust their behavior to changing circumstances can even be found in infants. Recent evidence showed that 15-mo-old infants exposed to stress kept performing a previously effective action, even after the action suddenly became ineffective, suggesting that stressed human infants tend to perform habitual behavior rigidly (Seehagen et al., 2015). These findings echo the well-established stress-induced switching from goal-directed to habitual control of action in rodents (see a more comprehensive review in Ref.…”
Section: Stressors Potentiate Decision Biasesmentioning
confidence: 99%
“…Whereas these data showed a shift in learning strategies at the behavioral level, fMRI data further revealed that stress may indeed induce a shift from hippocampal to dorsal striatal control of learning in the human brain (Schwabe & Wolf, ; Schwabe et al ., ). Similar to the stress‐induced modulation of hippocampal and dorsal striatal learning, stress has been shown to bias instrumental learning in favor of dorsal striatum‐dependent habit behavior and at the expense of PFC‐dependent goal‐directed action (Schwabe & Wolf, , ; Seehagen et al ., ). Together, these findings suggest that stress biases memory networks during learning toward simple but rather rigid memory processes.…”
Section: Focus On Changes In Memory Networkmentioning
confidence: 99%